Numerical study on instantaneous radial force of a centrifugal pump for different working conditions. Issue 2 (23rd November 2019) - Jia, Xiaoqi; Yuan, Sheng; Zhu, Zuchao; Cui, Baoling
Abstract : Purpose: Instantaneous radial force induced from unsteady flow will intensify vibration noise of the centrifugal pump, especially under off-design working conditions, which will affect safety reliability of pump operation in severe cases. This paper aims to conduct unsteady numerical computation on one centrifugal pump; thus, unsteady fluid radial force upon the impeller and volute is obtained, so as to study the evolution law of instantaneous radial force, the internal relationship between radial force and pressure pulsation, the relationship among each composition of radial force that the impeller received and the influence of leakage rate of front and back chamber on radial force. Design/methodology/approach: The unsteady numerical simulation with SST k-ω turbulence model was carried out for a low specific-speed centrifugal pump using computational fluid dynamics codes FLUENT. The performance tests and pressure tests were conducted by a closed loop system. The performance curves and the pressure distribution from numerical simulation agree with that of the experiment conducted. The unsteady pressure distributions and the instantaneous radial forces induced from unsteady flow were analyzed under different flow rates. Contribution degrees of three components of the radial force on the impeller and the relation between the radial force and leakage rate were analyzed. Findings: Radial force on the volute and pressure pulsation on the volute wall have the same distribution tendency, but in contrast to the distribution trend of the radial force on the impeller. In the component of radial force that the impeller received, radial force on the blade accounts for the main position. With the decrease of flow rate, ratio of the radial force on front and back casings will be increased; under large flow rate, vortex and flow blockage at volute section will enhance the pressure and radial force fluctuation greatly, and the pulsation degree may be much more intense than that of a smaller flow rate. Originality/value: This paper revealed the relation of the radial force and the pressure pulsation. Meanwhile, contribution degrees of three components of the radial force on the impeller under different working conditions as well as the relation between the radial force and leakage rate of front and rear chambers were analyzed.